A Study on Predicting ECT Signal of Tube Ding from Tube Support Plate Rotation During PWHT of Nuclear Steam Generator. (2015) - Kim, D.W.; Kim, J.C.; Kim, T.W.; Ko, G.B.
Abstract: During Post Weld Heat Treatment (PWHT) of nuclear steam generator fabricating process, there may occur permanent deformation on tube from rotation of Tube Support Plate (TSP) due to thermal deformation. The deformation called ding is strictly prohibited for the long-term integrity of steam generator. Non-acceptable tube ding is defined as deformation of which Eddy Current Testing (ECT) signal exceeds 0.5Volt. In this study the relationship between ECT signal and TSP rotation angle was established and the allowable rotation angle of TSP was determined. It will be used for air blowing control system to prevent tube ding damage.